A case study on the extensibility of network processor based systems - Ng, BK; Chieng, D; Abusin, AAYM; Uddin, MS (2005)
As the use of Internet become increasingly popular, diverse range of network applications which perform differently functions are needed to serve user's requirements. However, network system developers face problem to incorporate these new services in their products since the conventional network equipment architectures are monolithic, inflexible, costly and induce long development time. Thus, many developers begin to build their products based on network processor technology that promises more flexibility and therefore, an extensible system. In this paper, we study on the issues and considerations that involved in performing extension on network processor based system. In particular, we address this issue by adding a new building block into the existing router design using Intel IXP2400 network processor.